Pain assessment, management and impact among Hemodialysis patients: a study from Tunisia - Sanda Mrabet; Sandra Attia; Radhia Chaieb (BMC Nursing)
Abstract Introduction Pain is a common complication in patients with end-stage chronic kidney disease, impacting their quality of life. However, the pain experienced by dialysis patients is often overlooked in favor of other issues related to chronic kidney disease and dialysis itself. The study aimed to assess the prevalence, intensity, location, and impact of pain on daily activities in a cohort of chronic hemodialysis patients. Materials and Methods We conducted a cross-sectional study during November and December 2023. Patients aged 18 years and older, undergoing hemodialysis for at least 6 months, completed an anonymous questionnaire. Socio-demographic and clinical characteristics of the patients were recorded initially, and pain aspects were evaluated using the Brief Pain Inventory. Results Among the 100 patients surveyed, 78% reported suffering from chronic pain, considered moderate by 57.7% of them. Pain occurred in 89.7% of cases after hemodialysis sessions, was osteoarticular in 71.8% of cases, predominantly in the lower limbs in 94.9% of cases, of mixed type in 71.8% of cases, and caused partial functional impairment in 53.8% of cases. Paracetamol was the most commonly used analgesic (75% of cases). Conclusion This research confirms the high prevalence of pain among chronic hemodialysis patients and its negative impact on them. Healthcare providers should consistently evaluate pain in dialysis patients. Pain management should be a research priority because pain is a valid and considerable health concern in the increasing chronic kidney disease patient population.